The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1063/5.0024355
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous dynamics, correlated time and length scales in ionic deep eutectics: Anion and temperature dependence

Abstract: Heterogeneous relaxation dynamics often characterizes deep eutectic solvents. Extensive and molecular dynamics simulations have been carried out in the temperature range, 303 ≤ T/K ≤ 370, for studying the anion and temperature dependencies of heterogeneous dynamics of three different ionic acetamide deep eutectics: acetamide + LiX, X being bromide (Br−), nitrate (NO3−), and perchlorate (ClO4−). These systems are chosen because the fractional viscosity dependence of average relaxation rates reported by various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 100 publications
1
21
0
Order By: Relevance
“…Our analyses of RDFs have also depicted that the anions can interact simultaneously with acetamide and Li + leading to the complexities in these mixtures. 95,97 The monodentate anion Br − interacts in a completely different way than the tridentate planar NO 3 − . ClO 4 − being tetrahedral has one more interacting site, but its bigger size introduces some excluded-volume effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analyses of RDFs have also depicted that the anions can interact simultaneously with acetamide and Li + leading to the complexities in these mixtures. 95,97 The monodentate anion Br − interacts in a completely different way than the tridentate planar NO 3 − . ClO 4 − being tetrahedral has one more interacting site, but its bigger size introduces some excluded-volume effect.…”
Section: Resultsmentioning
confidence: 99%
“…Also, note that the structural heterogeneity of these mixtures has already been examined previously. 95,97 We investigated the structural heterogeneity part by a simulation of radial distribution functions and cluster size distributions among various interspecies. Although we did not calculate any order parameter 98 to quantify the structural heterogeneity, our analyses provided a molecular-level detailed description of the structural heterogeneity aspect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biswas et al [ 243 , 244 ] performed MD microstructure simulations for a number of Li salts (Li + , Br − , NO 3 − , ClO 4 − ) and acetamide to identify the solution-phase microstructures in these media, and investigated the anion and temperature dependence of these microstructures. The authors showed that the presence of heterogeneity arises from the balance of the interactions between the various species.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
“…Biswas et al [224,225] performed MD microstructure simulations for a number of Li salts (Li + , Br − , NO −3 , ClO −4 ) and acetamide to identify the solution-phase microstructures in these media, and investigated the anion and temperature dependence of these microstructures. The authors showed that the presence of heterogeneity arises from the balance of the interactions between the various species.…”
Section: Electrolyte-based Dessmentioning
confidence: 99%